(untitled) (Boca Raton, 2006)
Water Properties of Food, Pharmaceutical, and Biological Materials is based on information presented by leading researchers at the International Symposium on the Properties of Water in Foods (ISOPOW 2004). Chapters feature authoritative accounts of the latest research on the physical and chemical properties of water related to the stability of food, pharmaceutical, and biological materials. The book discusses the role of water in structural and functional properties and for preserving biomolecule functionality in restricted water environments. It also covers micro- and nano- techniques for assessing water-solid interactions in food and drug development.
Keywords: Food,Food; Water activity,Congresses,Moisture,Congresses